Retrospective evaluation of insulin degludec/insulin aspart co-formulation therapy in patients with type 2 Diabetes Mellitus: A single-center experience (Annals of Medical Research, 2021)
Aim: Insulin degludec/aspart (IDegAsp) co-formulation therapy is a novel drug in Turkey and the aim of this study was to retrospectively evaluate the effects of IDegAsp therapy on glycemic control and hypoglycemia in a single tertiary center in Turkey.Material and Methods: The medical records of patients with type 2 diabetes mellitus, who were evaluated at diabetes clinic of Cerrahpaşa Medical Faculty between January and April 2018 and had started to use IDegAsp, were investigated. The demographic characteristics of the patients, anti-diabetic medications they were currently using, causes of treatment change, the IDegAsp doses, fasting blood glucose (FBG), HbA1c and hypoglycemic episodes at treatment onset, the third and sixth months of therapy were evaluated.Results: Sixty-six patients (F/M:34/32; mean age:57.8±11,6years) were evaluated. Uncontrolled hyperglycemia (80.3%) and frequent hypoglycemic attacks (19,7%) were the causes of treatment change. IDegAsp was started as a single dose in 53% and double dose in 47% of patients. Sixty-two patients (93.9%) were using insulin and the number of injections were significantly reduced with IDegAsp (p0.001). There was no statistically significant difference in terms of insulin doses in sixth months of treatment (p=0.054), whereas FBG (p0.001), HbA1c (p0.001) levels and hypoglycemic attacks (p0.001) were reduced and the improvement in glycemic control occured particularly in the first 3 months of therapy.Conclusion: Glycemic control and hypoglycemic episodes were improved and the number of daily injections decreased with 6-months of IDegAsp treatment. IDegAsp, which is a novel drug for our country, may increase the treatment compliance of the patients and thus facilitate reaching the glycemic targets.